Ti-Al-C phase reinforced NiCrAlY composite coating as well as preparation method and application of Ti-Al-C phase reinforced NiCrAlY composite coating

By adding Ti-Al-C phase to the NiCrAlY coating, the enhanced phases such as Ti2AlC and TiC are formed, which solves the problem of low hardness of the coating in high-temperature wear environments, and the preparation of Ti-Al-C phase-enhanced NiCrAlY composite coating with high hardness and wear resistance is achieved, which significantly improves the high-temperature wear performance of the coating.

CN119506763AActive Publication Date: 2025-02-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411682370.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The existing NiCrAlY coating has low hardness in high-temperature wear environments, making it difficult to effectively prevent the wear and ash from adhesion of boiler pipe walls, increasing the risk of accidents such as pipe bursts.

Method used

By adding Ti-Al-C phase to the NiCrAlY coating, spray granulation and vacuum sintering are used to form enhanced phases such as Ti2AlC and TiC to improve the hardness and wear resistance of the coating.

Benefits of technology

The dense, high-hardness Ti-Al-C phase-enhanced NiCrAlY composite coating is achieved at low cost, significantly improving the performance of the coating in high-temperature wear environments and extending the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506763A_ABST
    Figure CN119506763A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating preparation, in particular to a Ti-Al-C phase reinforced NiCrAlY composite coating and a preparation method and application thereof.The Ti-Al-C powder is prepared through granulation, sintering and screening, the coating is prepared from 50%-70% of Ti-Al-C powder and 30%-50% of metal phase NiCrAlY, the atmosphere plasma spraying technology is adopted, the current ranges from 420 A to 480 A, the power ranges from 25 kW to 35 kW, the powder feeding rate ranges from 18 g / min to 24 g / min, the step pitch ranges from 3 mm, the main gas flow rate ranges from 35 L / min, the spraying distance ranges from 120 mm, and the Ti-Al-C phase reinforced NiCrAlY composite coating is prepared. And preparing the composite coating on the substrate. The application of the Ni-based composite thick coating in a high-temperature wear environment is realized, and the method for preparing the Ti-Al-C phase reinforced NiCrAlY composite coating at low cost is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating preparation, and in particular to a Ti-Al-C phase reinforced NiCrAlY composite coating, a preparation method and application thereof. Background Art

[0002] Coal is the main energy source in my country, and coal-fired power generation will remain the main power supply mode in my country for a long time in the future. Boilers are important energy conversion and carbon source conversion equipment, and their stable operation will be related to the stable development of the economy and society under the energy transformation policy. During the operation of power generation boilers, ash adhesion and wear are prone to occur, which will not only cause damage to the pipe wall, but also increase the risk of accidents such as pipe bursts.

[0003] Thermal spraying technology is a commonly used method for preparing surface protective coatings. Its spraying operation process is simple, the deposition efficiency is high, and the coating bonding strength is high. It can significantly improve the high-temperature wear resistance of the product and extend its service life. Coal-fired boiler coatings require coating materials to have excellent high-temperature stability, high-temperature wear resistance and good thermal conductivity. NiCrAlY coating has good high-temperature oxidation resistance, high-temperature stability and good thermal conductivity. However, the hardness of the coating is relatively low, and the addition of a reinforcing phase to improve the high-temperature wear performance of the coating is of great significance. We propose Ti-Al-C as a reinforcing phase addition system. On the one hand, the material system has low cost. On the other hand, by adjusting the process, the system can form a Ti with both thermal conductivity and wear resistance during the spraying preparation process. 2 AlC phase, and high hardness TiC reinforcement phase. Therefore, the preparation of a low-cost Ti-Al-C phase reinforced NiCrAlY composite coating and its application in high temperature wear environment have important application value.

[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to achieve the application of Ni-based composite thick coating in high temperature wear environment by reinforcing NiCrAlY coating by Ti-Al-C phase at low cost, and provide a Ti-Al-C phase reinforced NiCrAlY composite coating, a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention discloses a method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating, comprising the following steps:

[0007] S1, mixing Ti powder, Al powder and graphite with polyvinyl alcohol and sodium hydroxymethyl cellulose to obtain a slurry;

[0008] S2, spray granulating the slurry obtained in step S1 to obtain agglomerated powder, and then vacuum sintering, and sieving and grading the agglomerated powder after vacuum sintering to obtain Ti-Al-C powder;

[0009] S3, mixing the Ti-Al-C powder sieved in step S2 with NiCrAlY to obtain a mixed powder;

[0010] S4, performing sandblasting roughening treatment on the substrate;

[0011] S5, spraying the mixed powder on the substrate roughened in step S4 by using an aerated plasma spraying technique to prepare a composite coating.

[0012] In the step S1, the particle size distribution range of Ti powder, Al powder and graphite powder is Ti: 15-45 μm, Al 10 μm, C: 1-5 μm.

[0013] In the step S1, the molar ratio of Ti:Al:C is 2:1:1.

[0014] In the step S2, the sintering temperature of the vacuum sintering is 610-640°C.

[0015] In the step S2, the particle size of the Ti-Al-C powder obtained by sieving and classifying is 25-71 μm.

[0016] In the step S3, the mass ratio of Ti-Al-C powder is 60% to 80%.

[0017] In step S5, the process parameters of the atmospheric plasma spraying technology are: current 420-480A, power 25-35kW, powder feeding rate 18-24g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0018] The invention also discloses a Ti-Al-C phase reinforced NiCrAlY composite coating prepared by the preparation method and application of the Ti-Al-C phase reinforced NiCrAlY composite coating in a high temperature wear environment.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adopts a Ti-Al-C phase-reinforced NiCrAlY composite coating and its high-temperature wear application, the preparation method is simple, the cost is low, the obtained coating is dense, and it is tightly combined with the substrate. During the coating preparation process, reinforcing phases such as MAX phase and TiC are formed in situ, and it has good high-temperature wear performance, realizes the application of Ni-based composite thick coating in high-temperature wear environment, and provides a method for preparing Ti-Al-C phase-reinforced NiCrAlY composite coating at low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a bar graph of the bonding strength of the composite coating obtained in Example and Comparative Example 1;

[0021] Figure 2 is the wear rate of the composite coating obtained in Example and Comparative Example 1;

[0022] Figure 3 The XRD diagrams of the composite coatings obtained in Example 2 and Comparative Example 3 are shown;

[0023] Figure 4 The microhardness results of the coatings of Example 1, Comparative Example 2 and Comparative Example 3 are shown;

[0024] Figure 5 is the wear rate of the composite coating obtained in Example 1 and Comparative Example 2 and Comparative Example 3;

[0025] Figure 6 The cross-sectional morphology of the composite coating obtained in Example (a) and Comparative Example 4 (b);

[0026] Figure 7 is the wear rate of the composite coating obtained in Example and Comparative Example 4;

[0027] Figure 8 is the friction coefficient of the composite coating obtained in Example and Comparative Example 5;

[0028] Fig. 9 is the wear rate of the composite coating obtained in Example and Comparative Example 5;

[0029] Fig.10 is the wear rate of the composite coating obtained in Example and Comparative Example 6; DETAILED DESCRIPTION

[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0033] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0034] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio of 60% Ti-Al-C powder and 40% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0035] Step 4: Perform sandblasting roughening on the substrate.

[0036] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 30kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0037] Comparative Example 1

[0038] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0039] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0040] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio being 80% Ti-Al-C powder and 20% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0041] Step 4: Perform sandblasting to roughen the substrate.

[0042] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 30kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0043] Comparative Example 2

[0044] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0045] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0046] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio of 40% Ti-Al-C powder and 60% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0047] Step 4: Perform sandblasting to roughen the substrate.

[0048] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 30kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0049] Comparative Example 3

[0050] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0051] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0052] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio being 20% ​​Ti-Al-C powder and 80% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0053] Step 4: Perform sandblasting to roughen the substrate.

[0054] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 30kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0055] Comparative Example 4

[0056] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0057] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0058] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio of 60% Ti-Al-C powder and 40% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0059] Step 4: Perform sandblasting roughening on the substrate.

[0060] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 25kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0061] Comparative Example 5

[0062] Step 1: Ti powder, Al powder and graphite are mixed in a molar ratio of 2:1:1, and mixed with a binder and a dispersant to obtain a slurry.

[0063] Step 2: The slurry obtained in step S1 is spray granulated to obtain agglomerated powder, which is then vacuum sintered at a sintering temperature of 630° C. The agglomerated powder after vacuum sintering needs to be sieved and graded to obtain a particle size in the range of 25 to 71 μm.

[0064] Step 3: Mix the sieved powder in step S2 with NiCrAlY, with the ratio of 60% Ti-Al-C powder and 40% metal phase NiCrAlY powder, wherein the particle size of the NiCrAlY powder is 15-45 μm.

[0065] Step 4: Perform sandblasting roughening on the substrate.

[0066] Step 5: The composite coating was prepared on the substrate by atmospheric plasma spraying technology, and the process parameters were: current 460A, power 35kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0067] Comparative Example 6

[0068] The NiCrAlY coating was prepared on the substrate by atmospheric plasma spraying technology. The process parameters were: current 460A, power 30kW, powder feeding rate 20g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

[0069] Figure 1 It is a bar graph of the bonding strength of the embodiment and comparative example 1. It can be seen from the figure that when the Ti-Al-C content is too high, the bonding strength of the coating is poor, which affects the service stability of the coating.

[0070] Figure 2: is a bar graph of the wear rates of the embodiment and comparative example 1 at 600° C. The wear rate of the embodiment is lower than that of comparative example 1, and the wear performance is better than that of other comparative examples.

[0071] Figure 3 The XRD spectra of the coatings of Example 1, Comparative Example 2 and Comparative Example 3 show that MAX phase is formed in situ in the Example, and the main phases are TiC, Ni 3 Al and Ti 2 AlC, while in Comparative Example 2, because less Ti-Al-C content was added, no Ti 2 The formation of AlC phase is mainly Ni 3 Al phase, Ti 2 The absence of AlC phase affects the high temperature friction and wear properties of the coating.

[0072] Figure 4 The hardness bar graph of the coatings of Example 1, Comparative Example 2 and Comparative Example 3 shows that the maximum hardness value of the Example is 661.1 HV. 0.2 The hardness of the coatings in Comparative Examples 2 and 3 is lower than that in the embodiment.

[0073] Figure 5 The wear rate bar graph of the coatings in Example 1, Comparative Example 2 and Comparative Example 3 at 600°C is shown in Table 1. 2 The formation of AlC lubricating phase significantly reduces the wear rate of the coating by about 0.74×10 -15 m 3 / (N·m).

[0074] Figure 6 The cross-sectional morphology diagrams of the coatings of Example (a) and Comparative Example 4 (b) show that when the power is 30 kW, the coating is dense, free of defects such as cracks, and tightly bonded to the substrate. When the power is 25 kW, there are many unmelted particles in the coating and a small amount of holes appear.

[0075] Figure 7 It is a bar graph of the wear rate of the coatings of Example and Comparative Example 4 at 600°C. Since the spraying power of the coating of Comparative Example 4 is 25kW, there are more unmelted particles in the coating, and its wear rate is higher than that of the example.

[0076] Figure 8 4 is a histogram of the friction coefficient of Example 1 and Comparative Example 5 at 600° C. The friction coefficient of Example 1 is significantly lower than that of Comparative Example 4.

[0077] Fig. 9 The wear rate bar graph of Example and Comparative Example 5 at 600° C. The wear rate of Example is the lowest, and the wear performance is better than that of other comparative examples.

[0078] Fig.10The figure is a bar chart of the wear rates of the embodiment and comparative example 6 at 600°C. The wear rate of the embodiment is the lowest, and the wear performance is better than that of other comparative examples. Compared with the NiCrAlY coating of comparative example 6, the wear rate of the embodiment is greatly reduced. The present invention significantly improves the high-temperature friction and wear performance of the NiCrAlY coating, and realizes the application of the Ni-based alloy coating in the field of high-temperature friction and wear.

[0079] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating, characterized in that: The following steps are involved: S1, mixing Ti powder, Al powder and graphite with polyvinyl alcohol and sodium hydroxymethyl cellulose to obtain a slurry; S2, spray granulating the slurry obtained in step S1 to obtain agglomerated powder, and then vacuum sintering, and sieving and grading the agglomerated powder after vacuum sintering to obtain Ti-Al-C powder; S3, mixing the Ti-Al-C powder sieved in step S2 with NiCrAlY to obtain a mixed powder; S4, performing sandblasting roughening treatment on the substrate; S5, spraying the mixed powder on the substrate roughened in step S4 by using an aerated plasma spraying technique to prepare a composite coating.

2. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In the step S1, the particle size distribution range of Ti powder, Al powder and graphite powder is Ti: 15-45 μm, Al 10 μm, C: 1-5 μm.

3. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In the step S1, the molar ratio of Ti:Al:C is 2:1:

1.

4. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In the step S2, the sintering temperature of the vacuum sintering is 610-640°C.

5. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In the step S2, the particle size of the Ti-Al-C powder obtained by sieving and classifying is 25-71 μm.

6. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In the step S3, the mass ratio of Ti-Al-C powder is 60% to 80%.

7. The method for preparing a Ti-Al-C phase reinforced NiCrAlY composite coating according to claim 1, characterized in that: In step S5, the process parameters of the atmospheric plasma spraying technology are: current 420-480A, power 25-35kW, powder feeding rate 18-24g / min, step distance 3mm, main gas flow rate 35L / min, and spraying distance 120mm.

8. A Ti-Al-C phase reinforced NiCrAlY composite coating prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Ti-Al-C phase reinforced NiCrAlY composite coating as claimed in claim 8 in a high temperature wear environment.

Citation Information

Patent Citations

  • Method for preparing TiAl-based alloy

    CN102888530A

  • Wide-temperature-domain lubricant and abrasion-resistant composite coating and preparation and spraying methods thereof

    CN111349881A

  • TiAlCr anti-oxidation coating for TiAl alloy surface and preparation method of TiAlCr anti-oxidation coating

    CN113584416A

  • Method for preparing Ti-Al-C-based composite coating through plasma spraying

    CN115491629A

  • Copper alloy surface Ti-Al-C-based conductive wear-resistant composite coating and preparation method thereof

    CN118979217A